The Importance of Process and Outcome Assessment to Improve the Quality of Guidance and Counseling Services - Nurfarhanah; Dedi Effendi; Zadrian Ardi (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This research emphasizes the importance of assessing the process and outcomes of guidance and counseling to improve the quality of services in schools. Guidance and counseling (BK) services in schools play an important role in supporting students' overall development. Through a literature review approach, this research analyzes various evaluation models and practices applied in guidance and counseling programs. One of the models used is the CIPP (Context, Input, Process, Product) Model, which is one of the prominent and comprehensive models for assessing each element of guidance and counseling services. The results showed that active involvement in the evaluation of guidance and counseling teachers greatly influenced the effectiveness of the program. Regular assessments not only discover the strengths and weaknesses of the program, but also provide useful feedback for teachers' professional development. In addition, evaluations that involve parents and the community can improve the responsiveness of services to students' needs, especially in the midst of social changes and challenges faced in the digital era or industrial revolution 4.0. The study also emphasizes how important it is to use technology when assessing guidance and counseling activities. This is because it can improve the efficiency and effectiveness of the program. Therefore, it is clear that assessment of guidance and counseling processes and outcomes is crucial to providing quality, responsive, and flexible educational services. With the awareness of the importance of continuous evaluation, it is expected that guidance and counseling practices will change positively, which will help students' academic and personal growth.